Rancang Bangun Aplikasi Diagnosis Error Code Kerusakan pada Mesin ATM Berbasis Android - R. Yadi Rakhman Alamsyah; Reni Nursyanti; Muhammad Achya Arifudin; Muhammad Abdul Baqrik (Universitas Informatika dan Bisnis Indonesia, 2025)
An ATM that encounters a problem typically displays an indicator in the form of an error code. This code provides detailed information about the issue and instructions for resolving it. However, the detailed instructions can only be viewed on the ATM itself, making it difficult to analyze the problem outside the machine. If the ATM is located in a remote or inaccessible area, a solution is needed to facilitate remote analysis of the error code. To address this, an Android-based application has been developed to assist technicians in diagnosing faults and completing work reports. Data was collected through observation, interviews, and literature reviews, while system analysis utilized UML. The application was developed using PHP and MySQL, with tools such as Visual Studio Code and Flutter. The study concludes that this diagnostic application simplifies the process of diagnosing faults and filling out reports, thereby enhancing work efficiency and effectiveness.